Bengali Almanac : An Uncharted Area of Indian Mass Communication - Sah, Dr. Nilay Kumar (Delhi Khama Publishers, 2022)
Dr. Nilay Kumar Saha has completed this important study as part of the Indian Council of Historical Research 'Senior Academic Fellowship' scheme. This volume comprising 21 chapters covers almost all areas of cilvil society that were published in different Begali almanac either in the form of information or in the form of an advertisement
Keywords: Indian Mass Communication